Nonlinear Finite Element Analysis of Bone–Implant Contact in Three Short Dental Implant Models with Varying Osseointegration Percentages - Dawit Bogale Alemayehu; Masahiro Todoh; Song-Jeng Huang (Oral)
Objectives: Dental implants have become a cornerstone of restorative dentistry, providing a long-lasting method for tooth replacement. The degree of osseointegration has a significant effect on biomechanical stability at the bone–implant contact (BIC), determining the continued efficacy of these implants. However, the exact consequences of changing osseointegration levels on different implant designs, especially in bones with variable densities, are not well known. Methods: This study used 3D finite element analysis (FEA) to look at the biomechanical performance of three short dental implants: BioMet 3iT3, Straumann® Standard Plus Short-Regular Neck (SPS-RN), and Straumann® Standard Plus Short-Wide Neck (SPS-WN). This paper tested the implants at four stages of osseointegration: 25%, 50%, 75%, and 100% in both high-density (bone type III) and low-density (bone type IV) cancellous bone. It also created and examined realistic CAD models under static occlusal loading conditions to assess stress distribution and major strains at the bone–implant contact. Results: The study discovered that as osseointegration increases, von Mises stress and principal strains go down significantly for all implant types. The SPS-WN implant had the lowest strain values, especially for bone with low density. These reductions demonstrate increased mechanical stability as the bone–implant interface becomes more capable of dispersing mechanical stresses, minimizing the potential for localized deformation and bone resorption. Conclusions: The results highlight the importance of achieving optimum osseointegration to reduce mechanical stress and increase the lifespan of dental implants. The SPS-WN type implant performed better in biomechanical tests than the others, especially when bone conditions were not ideal. This makes it a great choice for clinical applications that need long-term implant success.